An Analysıs Of The Applıcatıon Thınk Aloud Protocol Strategy In Identıfyıng Students' Creatıve Thınkıng Skılls In Elementary Schools - Nurwalidainismawati; Azra Fauzi (Elementary Teacher Education Program, Majalengka University, 2024)
Creative thinking skills can encourage students to develop their thinking broadly, but in reality creative thinking skills will only develop if students practice continuously. Therefore, special strategies are needed to increase students' creativity, especially in learning mathematics. The aim of this research is to analyze the use of the Think Aloud Protocol strategy in identifying students' creative thinking abilities in elementary schools. This research uses qualitative research using a descriptive approach. The research subject was class V which was carried out in the odd semester of the 2023/2024 academic year. Data collection techniques through written tests and interviews. The validation process uses triangulation of sources and methods using 4 stages of analysis from Miles and Huberman. The results of the research showed that students in the very high creative thinking ability category mastered all 4 indicators of creative thinking ability, while those in the low creative thinking ability category mastered 1 of the 4 creative thinking ability indicators, this can be seen from their lack of fluency, flexibility, and lack of innovation in presenting. presentation of problem solving in questions. In conclusion, students' creative thinking abilities show different levels, especially in understanding the questions, describing the meaning of the questions, and explaining the answers to the questions. Therefore, involving students in habits of thinking will help students come up with different perspectives.